VLSI-SoC: Advanced research for systems on chip 19th IFIP WG 10.5/IEEE International conference on very large scale integration, VLSI-SoC 2011, Hong Kong, China, October 3-5, 2011, revised selected papers - Mir, Salvador (IFIP advances in information and communication technology, 2012)
This book contains extended and revised versions of the best papers presented at the 19th IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2011, held in Hong Kong, China, in October 2011. The 10 papers included in the book were carefully reviewed and selected from the 45 full papers and 16 special session papers presented at the conference. The papers cover a wide range of topics in VLSI technology and advanced research. They address the current trend toward increasing chip integration and technology process advancements bringing about stimulating new challenges both at the physical and system-design levels, as well as in the test of theses systems.